DNA: The Story of the Genetic Revolution - James Watson (Arrow Books, 2017)
Along with Francis Crick, James Watson was the discoverer of the double helix structure of the DNA molecule, realising both how it was able to reproduce itself and how, through its immense variety, it was able to pass on genetic instructions from one generation to the next. Their discovery paved the way for fifty years of explosive scientific achievement of extraordinary importance, both in strictly scientific terms and in its technological and social significance. From Dolly the sheep to GM foods to designer babies, science-related newspaper headlines have been dominated by the implications of their work. In DNA, now fully updated and revised to include new findings in gene editing, epigenetics and agricultural chemistry, as well as two entirely new chapters on personal genomics and cancer research, Watson tells the story of this pioneering research and its impact on the world in which we live, from its beginnings to the present day. This is the most comprehensive and authoritative exploration of DNA's impact - practical, social, and ethical - on our society and our world. Read more at https://www.penguin.co.uk/books/1035701/dna/#viabLqrbJzCkAMdi.99